The Effect of Art Therapy on Students' Learning Motivation at Madrasah Tsanawiyah: A Pre-Experimental Study with Wilcoxon Test - Wulandari, Dita; Ananda, Aulia Syalwa Risky; Zainuddin, Aulia Zahwa; Cahyani, Dwi Nadya (Seurune : Jurnal Psikologi Unsyiah, 2025)
This study investigates whether art therapy affects the learning motivation of students at Madrasah Tsanawiyah Islamiyah. A quantitative approach was employed, and data collected from pre-tests and post-tests were analyzed using the Wilcoxon Signed Rank Test. The sample consisted of 41 seventh and eighth-grade students from MTs Islamiyah. Based on the Wilcoxon test results, the calculated T value was 1.353, while the Z table value was 1.64. Thus, 1.353 1.64, indicating that H0 is accepted and H1 is rejected. Therefore, art therapy was not effective in increasing students' learning motivation.